DEVELOPING SMARTPHONE TECHNOLOGY TO DEVELOP STUDENT PSYCHOLOGY - Ausvina Ausvina; Ribka Wahyu Christiani; Yumi Yumi; Sari Sari; Lukas Lukas; Yesyurun Munthe (CV. ADIBA AISHA AMIRA, 2023)
The benefits of today's developments in information and communication technology are felt by many public. Mobile phones are one product of this technology that has changed behavior human communication across time and space. People thousands of kilometers away can each other communicate while looking at each other and only by using media cell phone. students in the city of Palangka Raya have also done so feel the impact of using this cellphone in communicating with friends, relatives, or people even in other areas. By using descriptive methods the author tries to determine the impact of use of mobile phones among people in the village. The results of the research, among other things, show that the use of cellphones does have a positive impact towards village communities, especially in order to maintain communication relations with people, especially relatives or family who are far outside the area. But within capacity As a smartphone with various features it has as a source of information, it turns out that this is not yet the case It is widely known about its use by the public.